The Effect of Knowledge, Environmental Awareness, Government Incentives and Perception of Benefits on the Interest in Buying Solar Panel in the Household Sector in Riau Province - Wisanta, Hosea; Pasaribu, Lamhot Henry (Dinasti Publisher, 2025)
This study aims to analyze the influence of Knowledge, Environmental Awareness, Government Incentives, and Perceived Benefits on the Purchase Intention of solar panel products in the household sector in Riau Province. The results show that Knowledge, Government Incentives, and Perceived Benefits have a positive and significant effect on Purchase Intention, while Environmental Awareness does not show a significant effect. Perceived Benefits is the most dominant variable influencing Purchase Intention. Simultaneously, the four independent variables explain 66.8% of the variation in Purchase Intention, while the remaining 33.2% is explained by other factors not included in this research model. These findings indicate that increasing public understanding, policy support, and positive perceptions of the benefits of solar panels play an important role in promoting the adoption of renewable energy at the household level.